Union of the Comoros : Enhanced Initiative for Heavily Indebted Poor Countries; Preliminary document. (IMF Staff Country Reports; Country Report ;, 2010)
Economic conditions in Comoros have yet to recover from the effects of persistent political instability and the recent global crises. Comoros's overall reform performance in the last two years constitutes encouraging first steps. Performance under the 2008/09 Emergency Post-Conflict Assistance (EPCA)- and Extended Credit Facility (ECF)-supported programs has been broadly satisfactory. The government's medium-term reform program, anchored in the Poverty Reduction Strategy Paper (PRSP), aims to invigorate economic growth and improve living conditions within a stable macroeconomic environment. Monetary and exchange rate developments will continue to be governed by the exchange rate peg under the Franc Zone arrangement.